2005
DOI: 10.1177/154405910508400714
|View full text |Cite
|
Sign up to set email alerts
|

Water Concentration in Self-etching Primers Affects their Aggressiveness and Bonding Efficacy to Dentin

Abstract: Water is required to ionize acid resin monomers for demineralization of tooth substrates. We tested the null hypothesis that altering the water concentration in two-step self-etching primers has no effect on their aggressiveness and bonding efficacy to dentin. Five experimental self-etching primers were prepared with resin-water-ethanol volume ratios of 9-0-1, 8-1-1, 7-2-1, 5-4-1, and 3-6-1. They were applied to smear-layer-covered dentin, followed by a bonding resin and composite build-ups for microtensile bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 24 publications
2
58
0
4
Order By: Relevance
“…With self-etching primers and adhesives, water is an indispensable component to the effective ionization of acidic adhesive monomers and suitable demineralization of dental hard tissues 5,23) . In the present study, the higher bond strength of SA-1 was suggested to be due to the ionized acidic adhesive monomers (i.e., 6-MHPA and 4-AET) that facilitated chemical interaction with hydroxyapatite [8][9][10] , thereby creating micromechanical retention [2][3][4][5] in the teeth to form strong adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With self-etching primers and adhesives, water is an indispensable component to the effective ionization of acidic adhesive monomers and suitable demineralization of dental hard tissues 5,23) . In the present study, the higher bond strength of SA-1 was suggested to be due to the ionized acidic adhesive monomers (i.e., 6-MHPA and 4-AET) that facilitated chemical interaction with hydroxyapatite [8][9][10] , thereby creating micromechanical retention [2][3][4][5] in the teeth to form strong adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, nanoleakage 23,24) defined as a leakage within hybrid layers, which occurred due to regions of incomplete resin infiltration has been reported. With regard to this problem, two-step self-etching primers and adhesives can adhere to enamel and dentin without the use of a separate acid-etching step [2][3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The adverse effect of one-step self-etch adhesive hydrophilicity on bonding to dentin has been reported. [8][9][10][11][12] In vitro dentin bond strength tests indicate that the hydrophilicity of one-step self-etch adhesives is a contributive cause for reduced short-term 13 and medium-term values.…”
Section: Introductionmentioning
confidence: 99%
“…Increased water concentration may indeed dilute the adhesive monomers and lower their inward rate of diffusion as well as limit the degree of polymerization. 22 In the present study, intrapulpal pressure was simulated during bonding and storage, which could intensify the negative effect of residual water retention.…”
Section: Discussionmentioning
confidence: 96%